2017
DOI: 10.1093/biolre/iox082
|View full text |Cite
|
Sign up to set email alerts
|

Genomic identification, expression profiling, and functional characterization of CatSper channels in the bovine†

Abstract: Cation channels of sperm (CatSper) are sperm-specific calcium channels with identified roles in the regulation of sperm function in humans, mice, and horses. We sought to employ a comparative genomics approach to identify conserved CATSPER genes in the bovine genome, and profile their expression in reproductive tissue. We hypothesized that CATSPER proteins expressed in bull testicular tissue mediates sperm hyperactivation and their rheotactic response in the reproductive tract of the cow. Bioinformatic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…It demonstrated (i) that stallion sperm respond to a fluid flow and also that their rheotactic response is affected by fluid viscosity (ii) it clearly illustrates for the first time that hyperactivated stallion sperm do not exhibit a rheotaxis-like behaviour and that their swimming pattern against a fluid flow is uncoordinated and non-progressive, similar to the erratic pattern traditionally observed in a static environment. In contrast, this study showed (iii) that both hyperactivated human and ram sperm do indeed display positive a rheotaxis-like behaviour, however, hyperactivated motility did not affect their rate of progression as it does in bull sperm 29 .…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…It demonstrated (i) that stallion sperm respond to a fluid flow and also that their rheotactic response is affected by fluid viscosity (ii) it clearly illustrates for the first time that hyperactivated stallion sperm do not exhibit a rheotaxis-like behaviour and that their swimming pattern against a fluid flow is uncoordinated and non-progressive, similar to the erratic pattern traditionally observed in a static environment. In contrast, this study showed (iii) that both hyperactivated human and ram sperm do indeed display positive a rheotaxis-like behaviour, however, hyperactivated motility did not affect their rate of progression as it does in bull sperm 29 .…”
Section: Discussioncontrasting
confidence: 81%
“…Although rheotaxis determination was not validated by a directionality method such as videomicroscopy, as described in other species 4 , 30 , 31 , this study has clearly shown that stallion sperm actively respond and adapt to fluid flow similar to human 4 and bull 29 and is in agreement with reported differences in the percentage of sperm exhibiting rheotaxis at different flow velocities in a microfluidic channel 25 . The only known published data on the rate of fluid flow in vivo is that by Miki and Clapham 4 who found the velocity of fluid flow within the oviduct of the mouse to be approximately 18 µm/s.…”
Section: Discussionsupporting
confidence: 80%
“…Epididymal spermatozoa from male CatSper ‐KO mice are incapable of exhibiting hyperactivation by incubation in the capacitation‐supporting medium . Although the CatSper channels exist in bull and boar ejaculated spermatozoa, further experiments are necessary to demonstrate their functions in the occurrence of hyperactivation.…”
Section: Regulatory Mechanisms For Flagellar Hyperactivationmentioning
confidence: 99%
“…Epididymal spermatozoa from male CatSper-KO mice are incapable of exhibiting hyperactivation by incubation in the capacitation-supporting medium 64,66,67. Although the CatSper channels exist in bull and boar ejaculated spermatozoa,68,69 further experiments are necessary to demonstrate their functions in the occurrence of hyperactivation.In bulls, boars, and mice, hyperactivation can be induced immediately in uncapacitated spermatozoa by a short treatment with putative stimulator for IP 3 R "thimerosal." The thimerosal-induced hyperactivation is full-type (bulls and boars)/anti-hock (mice) 38,50,51,70.…”
mentioning
confidence: 99%
“…CatSper glycoproteins form the sperm-specific voltage-gated Ca 2+ channels localised along the membrane of the sperm flagellum. CatSper channels contain glycoproteins that are involved in positioning regulation and recent work by our group has demonstrated that hyperactive bull sperm exhibit an increased rheotaxis response (Johnson et al, 2017). Targeted disruption of CATSPER 1, CATSPER2, CATSPER3 or CAT-SPER4 inhibits hyperactivated motility and thus rheotactic reponse (Johnson et al, 2017).…”
Section: Sperm Transport In the Female Tractmentioning
confidence: 99%